Biomechanical Basis for Treatment of Pediatric Foot Deformities Part I: Mechanics of the Foot: Current Concept Review - Varghese, Renjit A.; Rebello, Gleeson; Shah, Hitesh; Benjamin Joseph (Journal of the Pediatric Orthopaedic Society of North America, 2022)
The foot functions as a flexible structure during major part of the stance phase of the gait cycle but changes into a rigid structure in the terminal part of stance to enable a powerful push-off. This illustrated review describes the mechanics of the foot during inversion and eversion and explains in some detail how the calcaneum moves under a stationary talus in three planes simultaneously around a single oblique axis. The illustrations show how during eversion the calcaneum dorsiflexes, abducts and pronates while it plantarflexes, adducts and supinates during inversion. The talus remains static while the rest of the foot moves as a unit, referred to as the calcaneo-pedal unit (CPU), around the head of the talus. The socket-like hollow in the CPU consisting of the anterior and middle articular facets of the calcaneum, the articular fact of the navicular and the spring ligament constitute the “acetabulum pedis” which rotates around the talus. The foot, on occasion, functions like a twisted plate influencing the inter-relationship between the hindfoot and forefoot. This explains how a forefoot deformity may cause a secondary compensatory deformity of the hindfoot.